The Evolution of International Criminal Tribunals - M. Rhea, Harry (International Journal of Criminology and Sociology, 2017)
International criminal justice is a relatively new and uniquely distinct system of criminal justice. It combines international law and criminal law from various legal systems. Historically, international law applied only to States; however, it is now applied to individuals through its merging with criminal law. The majority of States have been genuinely unwilling or unable to prosecute those most responsible for the planning and commission of international crimes. This lack of genuine willingness to prosecute perpetrators of genocide, war crimes, and crimes against humanity has resulted in the recent creation of multiple international criminal tribunals. The emergence of international and quasi-international criminal tribunals should not reflect the assumption that the idea of such courts is new. On the contrary, the idea and discussions for creating international criminal tribunals have been with us for well over a century. This article traces the evolution of international criminal tribunals starting from 1864. Each major debate to establish an international criminal tribunal is closely analyzed. The article concludes with analysis of the International Criminal Court.